Pengembangan Lembaga Pendidikan Terintegrasi Nilai Sosial dan Budaya - Habibah; Nur Melinda; Zaskia; Suriagiri; Nur Effendi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to examine the development of educational institutions integrated with social and cultural values in creating a humanistic, adaptive, and socially relevant education system. The study employed a literature review method by analyzing journals, books, and scholarly articles related to social and cultural value-based education. The findings indicate that the integration of social and cultural values plays an important role in shaping students’ character, strengthening cultural identity, and increasing social awareness. In addition, the implementation of these values can create an inclusive and contextual learning environment. However, its implementation still faces challenges such as globalization, social change, and limited understanding of local culture. Therefore, strengthening culture-based curricula, improving educators’ competencies, and enhancing collaboration between schools and communities are necessary.